Effects of Physical Fitness Exercise, Mental Exercise and Mindfulness Exercise on Static and Dynamic Balance in Elderly Women - Latifeh Ghasempour; Fateme Sadat Hoseini; Mehran Soleymani; Malek Ahmadi (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives Elderly are exposed to balance dysfunction. This research aims at investigating the effect of physical exercises, mindfulness and mental training on static and dynamic balance in elderly women. Methods & Materials The participants included 60 women in the age group of 60-75 years who were categorized  into four groups randomly (three experimental groups "mindfulness, mental training, and physical exercises" and a control group, with 15 members in each group. To measure dynamic and static balance, Berg Balance Scale and Sharpened Romberg test were used. Experimental groups took part in physical exercise and mental training and mindfulness training sessions for eight weeks.  Each week had three sessions, and each session was of 75 minutes. Then the post-test was performed, and eight weeks after the post-test, a follow-up test was conducted. For data analyses, the variance for repeated measures and ANOVA test were used at 0.05 significant level. Results In the post-test balance scores (static and dynamic), there was no significant difference between mindfulness training and mental training groups (P<0.001). But the effects of mindfulness and mental training as compared to physical exercise and control groups were positive and significant (P<0.001). Besides, the effects of training in the physical exercise group were positive and significant compared to control group (P<0.001). In the follow-up test balance scores (static and dynamic), there was no significant difference between mindfulness training and mental training groups (P>0.05). Also, there was no significant difference between physical exercise and control groups. However, in comparison to physical exercise and control groups, the effects of mindfulness training and mental training were found to be positive and significant (P<0.001). Conclusion The study showed that physical exercises, mindfulness and mental training have a significant effect on the improvement of static and dynamic balance in elderly women, though the association of cognitive practices (mindfulness and mental training) with motor training (physical exercises) could cause a lasting impact. So, it is recommended to use physical exercises with cognitive training to improve static and dynamic balance in elderly people.